Religiusitas Guru PAI: Upaya Peningkatan Disiplin Beribadah Siswa di SMP Islam Al Azhar 3 Bintaro - Dewi Rokhmah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
PAI Teacher Religiosity: Efforts to Improve the Discipline of Student Worship at Al Azhar 3 Bintaro Islamic Junior High School. The purpose of this study was to determine the role of PAI teacher religiosity in an effort to increase the discipline of student worship at SMP Islam Al Azhar 3 Bintaro. Sources of data in this study were school heads, Islamic education teachers, and students. The technique of collecting data was done by means of interviews, observation, and documentation. The data obtained were analyzed using four steps, namely data collection, data reduction, data presentation, and verification or drawing conclusions. The results of this study indicate that the religiosity of PAI teachers at SMP Islam Al Azhar 3 Bintaro plays a role in increasing student discipline in worship characterized by congregational prayer, tahfdiz Quran, and tadarus which are routinely carried out properly and correctly. The application of PAI teacher religiosity in an effort to increase the discipline of student worship by providing motivation and exemplary.